NONPERFUSION AREA QUANTIFICATION IN BRANCH RETINAL VEIN OCCLUSION: A Widefield Optical Coherence Tomography Angiography Study. Issue 6 (June 2021) - Kadomoto, Shin; Muraoka, Yuki; Uji, Akihito; Tamiya, Ryosuke; Oritani, Yasuyuki; Kawai, Kentaro; Ooto, Sotaro; Murakami, Tomoaki; Iida-Miwa, Yuko; Tsujikawa, Akitaka
Abstract : Purpose: To precisely quantify retinal nonperfusion areas (NPAs) in branch retinal vein occlusion using widefield optical coherence tomography angiography (OCTA) and examine their association with neovascular complications. Methods: We enrolled 26 patients with treatment-naïve branch retinal vein occlusion and prospectively examined them for 12 months. After 3 monthly ranibizumab injections to treat macular edema, each patient underwent ultra-widefield (UWF) fluorescein angiography (FA) and OCTA. Ultra-widefield FA was additionally performed at Month 12. For UWF FA, the retinal NPA was measured using the equipment's built-in software. For OCTA, we used panoramic image montaged from 5 single 12 × 12 mm 2 images and quantified the retinal NPA using a Gullstrand eye with a grid scale at each patient. Measurements were expressed in terms of actual values and disc area units. Results: The retinal NPAs as measured using single OCTA and panoramic OCTA were significantly associated with that measured using UWF FA ( P < 0.001 for both). Retinal neovascularization lesions were observed in 4 (15.4%) of 26 eyes. For patients with accompanying neovascularization, the retinal NPA measured using UWF FA, single OCTA, and panoramic OCTA were 187.9 ± 39.5 mm 2 (109.9 ± 21.4 disc area), 34.3 ± 13.7 mm 2 (19.9 ± 7.7 disc area), and 106.6 ± 24.5 mm 2 (62.4 ± 13.6 disc area), respectively, which were larger than for those without neovascularization ( P < 0.001, 0.014, and <0.001, respectively). Conclusion: Using widefield OCTA, we could quantify the retinal NPA of eyes with branch retinal vein occlusion. These could serve as valid references to assess the risk of neovascular complications. Abstract : Supplemental Digital Content is Available in the Text.We quantified retinal nonperfusion area of eyes with branch retinal vein occlusion. In the evaluations, panoramic optical coherence tomography angiography and a Gullstrand model eye with a grid scale contributed to valid measurements. The measurement values could be new indexes for future neovascular complications.